Furniture Cost Estimate: Racquet Club Cottages, May 21, 1959 - Maurice Martiné Designs::::::author::: (1959)
Racquet Club Cottages West- Furniture Cost Estimate by Maurice Martiné; Job #5901-B; May 21st, 1959